2018
DOI: 10.1371/journal.pone.0197809
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the ecological and social targeting of a compensation scheme in Bangladesh

Abstract: Conservation payments are increasingly advocated as a way to meet both social and ecological objectives, particularly in developing countries, but these payments often fail to reach the ‘right’ individuals. The Government of Bangladesh runs a food compensation scheme that aims to contribute to hilsa (Tenualosa ilisha) conservation by improving the socioeconomic situation of households affected by hilsa sanctuary fishing bans. Analysing data from a household survey of compensation recipients and non-recipients,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This situation makes it difficult for fishers to provide for their families. In Bangladesh, fishers who received compensation during the temporal ban on fishing abstained from illegal fishing (Bladon et al, 2018). However, Corrêa et al (2014 found that due to the weak enforcement of the ban on fishing, fishers in the Brazilian Amazon continue to fish during the closed season despite receiving cash payments as compensation for abstaining from fishing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation makes it difficult for fishers to provide for their families. In Bangladesh, fishers who received compensation during the temporal ban on fishing abstained from illegal fishing (Bladon et al, 2018). However, Corrêa et al (2014 found that due to the weak enforcement of the ban on fishing, fishers in the Brazilian Amazon continue to fish during the closed season despite receiving cash payments as compensation for abstaining from fishing.…”
Section: Resultsmentioning
confidence: 99%
“…The conservation payment schemes could be in the form of cash payments or food items such as rice, sugar, cooking oil, etc., to cushion fishing households during the temporal ban on fishing. The Fishery officers must target the most vulnerable fishing households to achieve the objective of fisheries management (Bladon et al, 2018).…”
Section: Factors Of Closed-season Compliance Statisticsmentioning
confidence: 99%
“…Human population size also influences the extent of development and infrastructure, including agriculture and aquaculture, which place pressure on hilsa habitat ( BOBLME, 2011 ). In hilsa fishing areas, low income is associated with fishing juvenile hilsa (known in Bangladesh as jatka ) and with strong fishing dependence, which is characterised by illegal fishing and lack of other livelihood activities ( Bladon et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…We identified the primary economic activities in Bangladesh, and those which are fast-growing or being explored, and assessed trends in these activities. All of these activities are relevant to the hilsa fishery through the impacts of livelihood availability and wealth on fishing pressure ( Bladon et al, 2018 ). Some of them also have direct or indirect environmental impacts on hilsa populations: agriculture and aquaculture can affect hilsa habitat through eutrophication ( BOBLME, 2011 ): factories can contaminate rivers ( Karn and Harada, 2001 ); and mechanised vessels, shipbuilding, ship breaking, and oil and gas extractive industries can pollute coastal waters ( Chowdhury et al, 2017 ; Hossain et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finding a way to intercompare these diverse services from nature, from well-being and cultural importance to direct financial gain (e.g., from exploitation for industry) (Turner et al, 2003), is important for inclusive decision making and policy. For instance, in planning for development or conservation, such as through impact assessments and choosing among alternative courses of action (Nelson et al, 2009), and in addressing environmental degradation through equitable remediation, loss compensation, and resource allocation (Bladon et al, 2018). Throughout this paper, we refer to either values, ecosystem services, or both, depending on the context at hand.…”
Section: Introduction Why Value Sharks?mentioning
confidence: 99%